Le problematiche applicative della legge n. 194 del 1978 relative al diritto di obiezione di coscienza ancora a giudizio (Prime osservazioni alla decisione del Comitato Europeo dei Diritti Sociali nel caso CGIL contro Italia) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
This essay aims to analize the decision on the merit of collective complaint no. 91 of 2013 (CGIL v. Italy) of the European Committee of Social Rights and to take into account not only the actual violation of some articles of the European Social Charter, the consequences for the Italian legal system and the identification of some possible solutions and future prospects in the matter of conscientious objection in the voluntary termination of pregnancy, but also some specific aspects of the collective complaints’ procedure before the European Committee of Social Rights. Furthermore, the essay dwells on the innovative interpretation of the principle of non discrimination (art. E, European Social Charter), related to the right to health (art. 11, European Social Charter).
Keywords: health; work; conscientious objection; voluntary termination of pregnancy; European committee of social rights